Bimodal grain structure, phase transformation, and mechanical properties of a Mg-Gd-Y-Zn-Zr alloy during hot extrusion - Mingyang Chen; Hao Zhang; Liqing Wang; Kai Ma; DongDong Zhang; Yunlong Li; Shouzheng Wei; Zhen Zhang; Zhanyong Zhao; Peikang Bai (Journal of Materials Research and Technology)
In this study, we investigated the evolution of grain structures and second phases of a Mg-9.5Gd-4Y–2Zn-0.3Zr alloy during two-stage deformation that took place in the metal during hot extrusion, as well as their effects on its mechanical properties. We found that the alloy exhibited a bimodal grain structure consisting of equiaxed dynamic recrystallized (DRXed) grains and elongated unDRXed grains. As the extrusion process progressed, DRX occurred on a large scale, resulting in an increase in the proportion of DRXed grains from 17.8% to 93.2%, and a reduction in average grain size from 80.3 μm to 9.41 μm. The grain orientation also underwent a transition from a single orientation of an extrusion direction (ED) parallel to <0001> (i.e. ED//<0001>) to mixed orientations of ED//<01–10> and ED//<0001>. The primary mechanism of dynamic recrystallization (DRX) during extrusion involved particle-stimulated nucleation (PSN) accompanied by both continuous and discontinuous DRX. The Mg-9.5Gd-4Y–2Zn-0.3Zr alloy mainly contained intergranular 18R-long period stacking order (LPSO) phases and intragranular 14H-LPSO. As the extrusion process progressed, 18R-LPSO changed from blocky to lamellar to accommodate deformation, and β-Mg5(Gd,Y) phase particles dynamically precipitated along DRXed grain boundaries. The 14H-LPSO phase was found to be primarily distributed within coarse unDRXed grains. As deformation via extrusion progressed, the quantity of 14H-LPSO gradually decreased. Ultimately, with the gradual dissolution of Mg5(Gd,Y), 14H-LPSO reprecipitated within the recrystallized grain boundaries. As the extrusion process progressed, both the yield strength (YS) and elongation (EL) increased from 132.6 MPa to 287.6 MPa and from 10.8% to 15.5%, respectively. This was mainly attributed to the significant reduction in grain size and second phase size.